2014
DOI: 10.1007/s12550-014-0202-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of aflatoxins by Rhizopus oryzae and Trichoderma reesei

Abstract: This study evaluated the ability of the microorganisms Rhizopus oryzae (CCT7560) and Trichoderma reesei (QM9414), producers of generally recognized as safe (GRAS) enzymes, to reduce the level of aflatoxins B1, B2, G1, G2, and M1. The variables considered to the screening were the initial number of spores in the inoculum and the culture time. The culture was conducted in contaminated 4 % potato dextrose agar (PDA) medium, and the residual mycotoxins were determined every 24 h by HPLC-FL. The fungus R. oryzae ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
3
22
0
1
Order By: Relevance
“…The chromatographic parameters were a flow rate for the mobile phase 0.4 mL/min, and a column temperature of 45 C, resulting in a retention time of 12.5; 15.0; 18.5; and 22.4 min for AFLAG 2 , AFLAG 1 , AFLAB 2 and AFLAB 1 , respectively, at 25 min as a total running time. For the quantitation of the aflatoxins, the dry residue resulting from the extraction was dissolved with 0.2 mL of the mobile phase and manually injected on the HPLC-FL (Hackbart et al, 2014).…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
“…The chromatographic parameters were a flow rate for the mobile phase 0.4 mL/min, and a column temperature of 45 C, resulting in a retention time of 12.5; 15.0; 18.5; and 22.4 min for AFLAG 2 , AFLAG 1 , AFLAB 2 and AFLAB 1 , respectively, at 25 min as a total running time. For the quantitation of the aflatoxins, the dry residue resulting from the extraction was dissolved with 0.2 mL of the mobile phase and manually injected on the HPLC-FL (Hackbart et al, 2014).…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
“…Although this parameter was not able to describe the differentiation between active and inactive fungal biomass; it tended to increase during fermentation periods and correlated with the total amount of fungal biomass increasing (Hackbart et al, 2014). According to Figure 2, the result of the glucosamine content was depended on the fermentation days.…”
Section: Resultsmentioning
confidence: 97%
“…The fungal biomass in the fermented corn was determined by estimating the presence of glucosamine in the cell wall of the culture, modified from Hackbart et al (2014). Before entering the main glucosamine determining procedures, samples were treated as the modifying of Smits et al (1996a).…”
Section: Glucosaminementioning
confidence: 99%
See 1 more Smart Citation
“…Non-toxigenic fungus competes with close related strain to meet nitrogen, carbon, water and mineral (Ehrlich 2014). Rhizopus oligosporus (BCC F0216), Saccharomyces cerevisiae (BCC F0206) (Kusumaningtyas et al 2006), Rhizopus oryzae (CCT 7560) and Trichoderma reesei (QM9414) (Hackbart et al 2014) were also reported as biological control for Aspergillus flavus or aflatoxin.…”
Section: Introductionmentioning
confidence: 99%